(untitled) (Journal of Pharma Insights and Research, 2025)
Nanoemulsions are kinetically stable isotropic systems with droplet dimensions typically ranging between 20 and 200 nm, representing a transformative approach in pharmaceutical and industrial applications. Composed of oil, water, and stabilizing surfactants, these colloidal dispersions exhibit unique physicochemical properties such as enhanced optical clarity, substantial interfacial area, and robust kinetic stability. Their amalgamation into drug delivery protocols addresses critical challenges associated with the bioavailability of lipophilic compounds, facilitating efficient transport across biological barriers including the blood-brain barrier and dermal layers. The formation of these nanocarriers relies on fundamental principles involving either high-energy dispersion techniques or low-energy phase inversion methods, where the precise selection of oils and surfactant blends determines formulation stability and therapeutic efficacy. A diverse spectrum of administration routes ranging from parenteral and oral to topical and intranasal systems enables targeted therapeutic interventions in oncology, neurology, and dermatology. Apart from pharmaceuticals, the utility of these systems extends to nutraceuticals and cosmeceuticals, although successful commercialization necessitates rigorous long-term stability profiling